Exploring The Impact of Perceived Greenwashing on Repurchase Intention of Green Personal Body Care Products - Raihana, Jasmine; Purwanegara, Mustika Sufiati (Indonesian Journal of Business and Entrepreneurship, 2023)
Nowadays, brands from various industrial sectors have started to release new product line or branding strategy that focuses on preserving nature, one of the examples being green personal body care. The vague and excessive claims made by the brands evoked negative sentiment called perceived greenwashing as the consumers have a negative perception that the brand was deceiving them. This phenomenon is called greenwashing. The research aimed to understand the relationship between perceived greenwashing among Indonesian consumers with its consequences, such as word of mouth, green personal body care, attitude, and repurchase intention. A survey was conducted among Indonesian green personal body care consumers, receiving 108 valid responses in total. The data was later analyzed using descriptive analysis and PLS-SEM. The findings suggested a negative relationship between perceived greenwashing with word of mouth and green brand image. The two constructs were also the predictor of attitude toward green personal body care products. Attitude is the predictor of repurchase intention. The green brand image was also found to mediate the relationship between perceived greenwashing and attitude, also perceived greenwashing and repurchase intention. Keywords: green personal body care, perceived greenwashing, word of mouth, green brand image, repurchase intention